Degradation and inactivation of adenovirus in water by photo-electro-oxidation - Monteiro,G. S. (2015)
The present study analyzed the efficiency of the photo-electro-oxidation process as a method for degradation and inactivation of adenovirus in water. The experimental design employed a solution prepared from sterile water containing 5.107 genomic copies/L (gc/L) of a standard strain of human adenovirus type 5 (HAdV-5) divided into two equal parts, one to serve as control and one treated by photo-electro-oxidation (PEO) for 3 hours and with a 5A current. Samples collected throughout the exposure process were analyzed by real-time polymerase chain reaction (qPCR) for viral genome identification and quantitation. Prior to gene extraction, a parallel DNAse treatment step was carried out to assess the integrity of viral particles. Integrated cell culture (ICC) analyses assessed the viability of infection in a cell culture. The tested process proved effective for viral degradation, with a 7 log10 reduction in viral load after 60 minutes of treatment. The DNAse-treated samples exhibited complete reduction of viral load after a 75 minute exposure to the process, and ICC analyses showed completely non-viable viral particles at 30 minutes of treatment.